Os saberes docentes e a consciência fonológica: o que sabemos? O que ensinamos? - Barros, Zuleica Sousa (2024)
This work aims to evaluate the extent to which teacher training, regarding the development of children’s phonological awareness in literacy, is present in their didactic practice. The study was conducted with 12 literacy teachers who work in public schools in the city of São Luís, Maranhão. This research seeks, under a qualitative approach, in dialogue with quantitative research procedures, to raise the necessary data for the understanding of teaching knowledge related to phonological awareness. The research was organized in two moments: firstly, the collection of data on the profile and the survey of teachers’ conceptions, through the application of a questionnaire; and the second, observation and recording of the work developed in the classroom, as well as the analysis of the lesson plans. The present study is based on research related to phonological awareness, teacher training and reading and writing concepts with a focus on literacy and literacy practices in the early grades. The data analyzed reveal that the initial formation is a determining factor of the conceptions of reading and writing, especially those that focus on the work with the teaching practice based on the structure of the language. Furthermore, it was found that, of the phonological awareness content worked on in class, the syllable is the most representative.